2011
DOI: 10.1021/jf201728p
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Supramolecular Structures on Thermoplastic Zein–Lignin Bionanocomposites

Abstract: The effect of alkaline lignin (AL) and sodium lignosulfonate (LSS) on the structure of thermoplastic zein (TPZ) was studied. Protein structural changes and the nature of the physical interaction between lignin and zein were investigated by means of X-ray diffraction and Fourier transform infrared (FT-IR) spectroscopy and correlated with physical properties. Most relevant protein structural changes were observed at low AL concentration, where strong H-bondings between the functional groups of AL and the amino a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 31 publications
5
54
0
Order By: Relevance
“…Lignin is one of the most abundant non-toxic, amorphous, natural biopolymers, second only to cellulose (Lundquist and Parkas 2011;Oliviero et al 2011;Sahoo et al 2011). It serves as a continuous matrix component in plant cell walls, providing mechanical strength and structural support (Ibrahim et al 2011;Rozman et al 2011;Silva et al 2011;Yue et al 2011Yue et al , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Lignin is one of the most abundant non-toxic, amorphous, natural biopolymers, second only to cellulose (Lundquist and Parkas 2011;Oliviero et al 2011;Sahoo et al 2011). It serves as a continuous matrix component in plant cell walls, providing mechanical strength and structural support (Ibrahim et al 2011;Rozman et al 2011;Silva et al 2011;Yue et al 2011Yue et al , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…The shift to lower frequencies, or the disappearance of peak, could be attributed to the insertion of lignin component in the both secondary structure conformations and the corresponding formation hydrogen bondings between amino-acid-zein and functional groups of lignin. 24 As reported by Oliviero et al, 24 the reduction of aminoacid-aminoacid interactions in the zein secondary structure, induced by insertion of small molecules, was already observed by several authors. 25,26 Conversely, at high lignin content an increase of peak wavenumber for ordered conformations and a decrease of peak wavenumber for disordered conformations was observed, due to higher number of interaction between zein structure and lignin functional groups.…”
Section: Resultsmentioning
confidence: 57%
“…The measured FT-IR spectra were deconvoluted in the region (800-1600 cm À1 ) related to the 'Amide I' frequency range. 23,24 In this region, the assignment of the ordered phases (-sheet and -helix) and disordered phase (-turns) stretching vibrations at 1623, 1651 and 1676 cm À1 , respectively, was done according to Rahmelow et al 21 and Singh et al 23 Results showed that the presence of both AL and LSS induced shifting in frequencies of band corresponding to different secondary conformations (Figure 4(a) and (b)). In particular, for samples with low lignin concentration, it is possible to observe an overall shift towards lower vibration frequency for -helix, the disappearance of absorption peaks for -sheet conformations and a corresponding shift towards high frequency for -turns.…”
Section: Resultsmentioning
confidence: 99%
“…The glass transition temperature (T g ) was measured using dynamic mechanical tests according to Oliviero et al [20] using a DMA Tritec 2000 (Triton Technology, U.K.) in tensile-deformation mode. Temperature scan tests were performed by applying a tensile displacement of 10 lm at a frequency of 1 Hz and a heating rate of 4°C/min from -80 to 120°C.…”
Section: Dmamentioning
confidence: 99%